Comprehensive virome analysis of Varroa destructor populations in South Korea - Kim, Ji-Young; Moon, Kyung Hwan; Kim, Young Ho; Eliash, Nurit; Yoon, June-Sun (Frontiers in Insect Science, 2026)
The ectoparasitic mite Varroa destructor and the viruses it transmits pose a significant threat to honey bee health (Apis mellifera), contributing to colony collapse disorder. In this study, a metatranscriptomic analysis of V. destructor from six regions in South Korea was conducted to characterize its viral communities. Using high-throughput sequencing (HTS), we identified 16 known viruses and classified them into three groups: honey bee-pathogenic, Varroa destructor viruses (VDVs), and viruses with unknown hosts. Reverse transcription polymerase chain reaction (RT-PCR) was used to validate the HTS results, revealing only two discrepancies out of 96 comparisons. This emphasizes the importance of integrating both methods for comprehensive virome analysis. Deformed wing virus was the most prevalent and abundant virus, comprising 75%–99% of viral reads in five out of six farms. One farm showed a high abundance of VDVs (3 and 9). Notably, two previously unreported viruses with unknown hosts, Hubei partiti-like virus 34 and Lilac leaf chlorosis virus (LLCV), were identified. For LLCV, the detection of all ribonucleic acid segments highlighted the critical impact of sequencing depth on viral genome analysis. To our knowledge, this study provides the first virome characterization of V. destructor in South Korea, revealing diverse viral communities. It also proposes an integrated analytical approach using RT-PCR and HTS, emphasizing the importance of sequencing depth. This analysis provides valuable insights into the potential impacts of viral infections on honey bee colony health and the epidemiology of viral transmission.